2009
DOI: 10.1177/0022034508328626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Liquid Diet on Temporomandibular Joint Mechano-receptors

Abstract: Load during mastication is an important factor for the development and maintenance of mechano- receptor properties. The purpose of this study was to examine property changes in the rat TMJ mechano-receptors under conditions of liquid diet feeding and low articular load during the growth period. The hypothesis was that alterations in mastication of liquid diet might increase TMJ mechano-receptor sensitivity. Sixty-six two-week-old male Wistar rats were divided into two groups: a control group that was fed on wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Also, the response properties of rat periodontal mechanoreceptors and temporomandibular joint mechanoreceptors attain maturation by the age of 5 weeks (Nasution et al, 2002; Ishida et al, 2009). Since each receptor of the trigeminal nerve endings complete maturation at 5 weeks of age, nasal obstruction at this point is expected to have a significant effect on the stomathognatic system.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the response properties of rat periodontal mechanoreceptors and temporomandibular joint mechanoreceptors attain maturation by the age of 5 weeks (Nasution et al, 2002; Ishida et al, 2009). Since each receptor of the trigeminal nerve endings complete maturation at 5 weeks of age, nasal obstruction at this point is expected to have a significant effect on the stomathognatic system.…”
Section: Discussionmentioning
confidence: 99%
“…The response properties of TMJ mechanoreceptors change in association with an altered masticatory environment such as low masticatory function. 16 For instance, a change in the consistency of food to a liquid diet has been reported to increase the physiologic response of the TMJ, resulting in a continuous decrease in the threshold of the TMJ units. 16 In this study, the threshold of TMJ units decreased during the first phase and then increased to the original level during the second phase.…”
Section: Discussionmentioning
confidence: 99%
“…16 For instance, a change in the consistency of food to a liquid diet has been reported to increase the physiologic response of the TMJ, resulting in a continuous decrease in the threshold of the TMJ units. 16 In this study, the threshold of TMJ units decreased during the first phase and then increased to the original level during the second phase. Although it appears as though the physiologic function of the TMJ was reduced during the first phase, it recovered to show a normal response during the second phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensory neurons that supply the TMJ are classified as either mechanoreceptive or nociceptive neurons. It has been shown that the response properties of TMJ‐mechanoreceptive neurons change after feeding with a liquid diet . The nociceptive system provides warning signals to identify internal and external noxious stimuli and is a basic physiological defense mechanism.…”
Section: Introductionmentioning
confidence: 99%